The Symbols and Myths of Rice in Sasak’s Culture: A Portrait of Hybrid Islam in Lombok - Saharudin Saharudin (Al-Jami'ah Research Centre, 2019)
This article aims at discussing two important points of rice ethnophilosophy in Sasak society. First, it explains how various symbols of language and culture and local mythos of rice in agricultural Sasak society experienced reinterpretation over key concepts of Islamic Worldview. Second, it illuminates how those modified symbols and mythos in Sasak society contains similarities with the ones in Malay culture as recorded in Hikayat Asay Pade manuscript and Kitab Berladang. The study uses ethnohermeneutic method in reading the text in the context of Sasak culture. The result shows some points of transformation in the symbols and mythos about rice in Sasak culture after being adapted to Islamic Worldview. The reinterpretation clarifies a spirited ethnophilosophy about harmony and equilibration of human life with nature and God. Adaptation conducted by the Islamic carrier among the agricultural Sasak society at the beginning of Islamic influence exemplifies how the spreading of Islam was undertaken peacefully through the confirmation of symbols and local mythos to maintain stability and harmony.[Tulisan ini mendiskusikan tentang simbol (bahasa dan budaya) dan mitos padi lokal dalam masyarakat Sasak agraris yang mengalami reinterpretasi setelah konsep-konsep kunci Islamic worldview mulai diadaptasi dan disebarkan oleh para penyebar Islam awal di kalangan petani tradisional. Selanjutnya, didiskusikan pula tentang persinggungan simbol dan mitos lokal Sasak tersebut (setelah mengalami reinterpretasi dengan konsep-konsep kunci Islam) dengan budaya Melayu yang terekam dalam manuskrip Hikayat Asay Pade dan Kitab Berladang. Berdasarkan hasil pembacaan dengan metode etnohermeneutik dapat dipahami tentang apa saja hasil reinterpretasi masyarakat Sasak agraris mengenai simbol dan mitos padi lokal setelah mengalami persentuhan dan penyesuaian dengan Islamic worldview. Hasil reinterpretasi tersebut menjelaskan pandangan budaya (etnofilosofi) yang sangat bernas tentang harmonisasi dan keseimbangan hidup manusia dengan Tuhan dan alam. Selain itu, adaptasi yang dilakukan oleh penyebar Islam awal di kalangan masyarakat Sasak agaris ini merupakan contoh bagaimana Islam disebarkan dengan damai dan adaptif terhadap simbol dan mitos lokal supaya keseimbangan dan keharmonian tetap terjaga.]